2019
DOI: 10.1177/2055668319869517
|View full text |Cite
|
Sign up to set email alerts
|

What do we require from surveillance technology? A review of the needs of people with dementia and informal caregivers

Abstract: IntroductionDementia has become a major global concern and surveillance technology might provide support for informal caregivers and people with dementia. However, the needs of caregivers and people with dementia for surveillance technology have not been reviewed.MethodA scoping literature review was used to identify the needs of caregivers and/or people with dementia towards surveillance technology. Electronic database searching was undertaken on LexisNexis, PubMed, Scopus, EMBASE, MEDLINE, Cumulative Index t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 49 publications
(205 reference statements)
0
42
0
Order By: Relevance
“…and not dementia specific. In fact, recent systematic reviews of community engagement in the development of dementia care technology 25 , 26 show that the omission of ethnicity and rurality as variables, has been common in this field. In the present study, intentionally engaging six rural Indigenous communities in Canada led to firmware and hardware design issues that might not have otherwise been evident among urban participants or contexts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…and not dementia specific. In fact, recent systematic reviews of community engagement in the development of dementia care technology 25 , 26 show that the omission of ethnicity and rurality as variables, has been common in this field. In the present study, intentionally engaging six rural Indigenous communities in Canada led to firmware and hardware design issues that might not have otherwise been evident among urban participants or contexts.…”
Section: Discussionmentioning
confidence: 99%
“…In this work however, the ethnicity of participants was rarely identified in any of the cited studies, nor was culture considered as a driving force behind context. 26 Our research objective is the development of culturally safe and culturally designed technology capable of tracking an Indigenous older adult with declining cognitive health in rural and remote areas in such a way that their mobility and independence is not impaired, connection to cell towers or internet is not needed, and the information reported from the device is useful to families to facilitate aging-in-place.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review by Vermeer et al [ 27 ] indicated that research on the needs of older people living with dementia and their caregivers remained mainly qualitative, with more focus on the needs of caregivers than patients and a clear difference in perspectives. For instance, results from focus groups revealed that dementia patients had some concerns over the use of trackers, while their caregivers had a great interest in their use [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence rates of PwDs getting lost even in familiar environments range from 17% (6) to 75% (7) depending on de nitions and reporting measures used, which exposes PwDs to risks that can result in life-threatening circumstances (9). To avoid such risks, CGs' often limit PwDs' independent outdoor ambulation by opting for chaperon, sedative or incarceration-type prevention measures (10) although these measures can negatively impact biopsychosocial health (11). By contrast, locating devices can promote PwDs' independence and safety by helping them manage spatial orientation impairments and by supporting CGs to intervene when necessary (12).…”
Section: Introductionmentioning
confidence: 99%